The Relation of Menopause Duration with Estrogen Hormone Levels in Menopause Women 1-5 Years in Sukoanyar Village, Pakis District, Malang. - Eny Rahmawati; Erwanto; Desy Rinawaty (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Menopause is the cessation of the physiological process of the menstrual cycle which is related to a woman's age. Permanent cessation of the menstrual cycle is caused by loss of activity of the ovarian follicles which is expressed when experiencing amenorrhea (no menstruation) for 12 months. The aim of this study was to determine the relationship between the duration of menopause and estrogen hormone levels in menopausal women 1-5 years in Sukoanyar Village, Pakis Malang District. This research was conducted in December 2023. This research is a quantitative descriptive study with a cross sectional approach, the sample size in this study was 93 respondents. Based on the frequency distribution, respondents who experienced menopause within 2 years were the respondents with the largest percentage, namely 29%. The frequency distribution of respondents based on estrogen levels ≥130 pg/mL was 42 respondents or 45.2%, while estrogen levels ≤ 130 pg/mL were 51 people or 54.8%. Meanwhile, based on the Pearson test, the Sig (tailed) value or p value was 0.509, which means the relationship between estrogen levels and length of menopause is said to be not significant. And based on the correlation value, it shows that the correlation level is very low